Combined experimental and theoretical study of the structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 - Jana, Manoj K.; Singh, Anjali; Late, Dattatray J.; Rajamathi, Catherine R.; Biswas, Kanishka; Felser, Claudia; Waghmare, Umesh V.; Rao, C. N. R. (Journal of Physics-Condensed Matter, 2015)
The recent discovery of non-saturating giant positive magnetoresistance has aroused much interest in Td-WTe2. We have investigated structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 experimentally and theoretically. Spin-orbit coupling is found to govern the semi-metallic character of Td-WTe2 and its structural link with the metallic 1 T form provides an understanding of its structural stability. There is a metal-to-insulator switch-over in the electrical conductivity and a change in the sign of the Seebeck coefficient around 373 K. Lattice vibrations of Td-WTe2 have been analyzed using first-principles calculations. Out of the 33 possible zone-center Raman active modes, five distinct Raman bands are observed around 112, 118, 134, 165 and 212 cm(-1) in bulk Td-WTe2. Based on symmetry analysis and calculated Raman tensors, we assign the intense bands at 165 cm(-1) and 212 cm(-1) to the A(1)' and A(1)'' modes, respectively. Most of the Raman bands stiffen with decreasing thickness, and the ratio of the integrated intensities of the A(1)'' to A(1)' bands decreases in the few-layer sample, while all the bands soften in both the bulk and few-layer samples with increasing temperature.
Keywords: Raman spectroscopy; Td-structure; tungsten ditelluride

Low frequency noise and photo-enhanced field emission from ultrathin PbBi2Se4 nanosheets - Suryawanshi, Sachin R.; Guin, Satya N.; Chatterjee, Arindom; Kashid, Vikas; More, Mahendra A.; Late, Dattatray J.; Biswas, Kanishka (Journal of Materials Chemistry C, 2016)
Atomically thin two-dimensional layered materials have gained wide interest owing to their novel properties and potential for applications in nanoelectronic and optoelectronic devices. Here, we present the spectral analysis and photo-enhanced field emission studies of a layered intergrowth PbBi2Se4 nanosheet emitter, performed at the base pressure of similar to 1 x 10(-8) mbar. The emitter shows a turn-on field value of similar to 4.80 V mu m(-1), corresponding to an emission current density of similar to 1 mu A cm(-2). Interestingly, when the cathode was illuminated with visible light, it exhibited a lower turn-on field of B3.90 V mm(-1), and a maximum emission current density of similar to 893 mu A cm(-2) has been drawn at an applied electric field of similar to 8.40 V mu m(-1). Furthermore, the photo-enhanced emission current showed reproducible, step-like switching behavior in synchronous with ON-OFF switching of the illumination source. The emission current-time plots reveal excellent stability over a duration of similar to 6 h. Low-frequency noise is a significant limitation for the performance of nanoscale electronic devices. The spectral analysis performed on a Fast Fourier Transform (FFT) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha similar to 0.99. The low frequency noise, photo-enhanced field emission, and reproducible switching behavior characterized with very fast rise and fall times propose the layered PbBi2Se4 nanosheet emitter as a new promising candidate for novel vacuum nano-optoelectronic devices.